2021
DOI: 10.15627/jd.2021.19
|View full text |Cite
|
Sign up to set email alerts
|

Measurement, Simulation, and Quantification of Lighting-Space Flicker Risk Levels Using Low-Cost TCS34725 Colour Sensor and IEEE 1789-2015 Standard

Abstract: Building owners are transitioning towards a smart lighting solution for illumination purposes. LED (Light Emitting Diode) lighting application has become a norm given its high efficacy and energy efficiencies. This paper presents an approach to monitor the percent flicker conformance of interior building lighting to international standards. The focus is on flickers induced by LED lightings. This experiment utilises a TCS34725 RGB (red, green, blue) colour sensor to measure the flicker parameters of interior li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…According to all investigations, the optimal combination of CCF is CCFT2 with a 53/23 LE coating. The current study also demonstrated the quality of results obtained by the CCFT4 group with 58/83 nanocoating with silver reflector in a humid tropical climate, as recommended by other researchers [32][33][34][35]. In addition, Table 5 reveals that the percentage of improvement in the studies is very close to the annual results; however, this study revealed a relatively greater improvement in the humid tropical climate.…”
Section: Ccf-tgu With Configuration Year-round Performancesupporting
confidence: 83%
“…According to all investigations, the optimal combination of CCF is CCFT2 with a 53/23 LE coating. The current study also demonstrated the quality of results obtained by the CCFT4 group with 58/83 nanocoating with silver reflector in a humid tropical climate, as recommended by other researchers [32][33][34][35]. In addition, Table 5 reveals that the percentage of improvement in the studies is very close to the annual results; however, this study revealed a relatively greater improvement in the humid tropical climate.…”
Section: Ccf-tgu With Configuration Year-round Performancesupporting
confidence: 83%